Efektivitas Model Direct Instruction untuk Meningkatkan Kemampuan Pengurangan Bilangan Bagi Peserta Didik Disabilitas Intelektual Ringan - Efendi, Ananda Tiara Septia; Irdamurni, Irdamurni; Marlina, Marlina; Efrina, Elsa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to observe the improvement of the ability to subtract lower numbers for mild mentally disabled students in phase B of SLB Kemala Bhayangkari Lintau Buo after using the Direct Instruction model. The type of this study is Single Subject Research (SSR) with an A-B-A design. The baseline phase (A1) was conducted in four sessions, aiming to obtain initial data on students' abilities. This is followed by the intervention phase (B), which was conducted over eight sessions using the Direct Instruction model. Finally, a second baseline phase (A2) was conducted for four meeting sessions to evaluate the sustained impact of the intervention. Data collection was performed through performance testing techniques using an instrument in the form of a checklist to record the students' performance results. Data analysis was then conducted using visual graphic techniques. The research results show that at the baseline condition (A1), the results obtained were 10%, 15%, 30%, 35%, 40%, 50%, 70%, 70%. Meanwhile, at the baseline condition (A2), the results were 75%, 85%, 95%, 95%. Based on the data analysis results, this study indicates that the ability to perform subtraction in students with mild intellectual disabilities improved after the implementation of the Direct Instruction learning model. Therefore, it can be concluded that the Direct Instruction model is effective in enhancing the ability to perform subtraction in students with mild intellectual disabilities during the intervention phase (B) at SLB Kemala Bhayangkari Lintau Buo.